Báo cáo tóm tắt thẩm tra về quyết toán ngân sách nhà nước năm 2019 (Số: 10/BC- UBTCNS15) - UBTCNS (2021)
Toàn văn Báo cáo tóm tắt thẩm tra về quyết toán ngân sách nhà nước năm 2019 (Số: 10/BC- UBTCNS15)